THE IMPLEMENTATION OF COLLABORATIVE STRATEGIC IN STUDENTS’ READING COMPREHENSION AT SMA NEGERI 3 TONDANO - Mudihang, Trisyen; Liando, Nihta V. F; Hampp, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to address the following research topic: Does the use of Collaborative Strategy Reading (CSR) affect how well class XI IPA 1 student understand recount texts? This essay aims to demonstrate how group reading strategies impact students’ comprehension of recount texts. Data from a reading test comprising 40 numerous questions and 10 question types were gathered for the purposes of this quantitative study. This pre-experimental study used a one-group pretest-posttest design. For such 2022–2023 academic year, 32 students from Tondano’s XI IPA 1 SMA Negeri 1 class took part in this activity. The information was gathered using descriptive statistics, which were then analyzed using statistical analysis. Data analysis produced the following conclusions: In these other words, the kid performed better on the reading portion of the test after treatment than before. (1) In the pre-test, 80 was the highest score and 50 was the lowest; in the post-test, 100, or a perfect score, was the highest score and 70 was the lowest. (2) The post-average test was 81.41, which was greater than the pre-average test of 62.96. This is because it can be demonstrated the students’ reading performance on the pre-test or post-test before treatment is more diverse than on the test after treatment using Collaboration Strategy Reading (CSR) calculations and the standard deviation